The Viking Process - Hartley, Norman (New York Simon and Schuster, 1976)
(3z(BThe Viking Process(3y (Bis a 1976 techno-terrorism novel. The protagonist, Philip Russell, is an expert on terrorism and urban guerrilla warfare. While on an international trip to speak at a conference on the terrorism war, he decides to go to a movie, where he meets Michelle, a young and very seductive woman. He goes to bed that night a faithful married man, loses his loyalty card, and wakes up to find himself blackmailed by a dark side organization called the ISC$1 (Bthe Institute for Social Change.s
Keywords: Fiction